1997
DOI: 10.1200/jco.1997.15.5.1923
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of thymidylate synthase expression in early breast cancer.

Abstract: In early-stage breast cancer, high TS expression is associated with a significantly worse prognosis in node-positive patients. Node-positive patients with high TS levels demonstrate the most significant improvement in DFS and OS when treated with six cycles of conventional adjuvant CMF therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
87
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 14 publications
7
87
4
Order By: Relevance
“…Thirdly, it is also possible that adjuvant chemotherapy did not affect survival regardless of TS expression, which may explain the lack of difference in survival between high-TS and low-TS groups in the current study. Alternatively, there is a possibility that the gastric cancer patients with high TS expression might experience a greater survival benefit from adjuvant chemotherapy compared to patients with low TS expression, as shown in other studies with rectal cancer and breast cancer (Johnston et al, 1994;Pestalozzi et al, 1997). In the current study, there was no significant difference in survival according to important prognostic variables such as Lauren's classification, lymph node metastasis and pathologic stage.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thirdly, it is also possible that adjuvant chemotherapy did not affect survival regardless of TS expression, which may explain the lack of difference in survival between high-TS and low-TS groups in the current study. Alternatively, there is a possibility that the gastric cancer patients with high TS expression might experience a greater survival benefit from adjuvant chemotherapy compared to patients with low TS expression, as shown in other studies with rectal cancer and breast cancer (Johnston et al, 1994;Pestalozzi et al, 1997). In the current study, there was no significant difference in survival according to important prognostic variables such as Lauren's classification, lymph node metastasis and pathologic stage.…”
Section: Discussionmentioning
confidence: 96%
“…The discrepant findings between the current study and the previous reports in terms of prognostic implications of TS could be explained as follows. First, the TS expression in primary tumours of gastric cancer patients may not reflect the ability of the tumour to induce TS protein or undergo TS gene amplification with exposure to chemotherapeutic agents (Johnston et al, 1994;Pestalozzi et al, 1997). Secondly, all patients in this study were treated with doxorubicin as well as 5-FU, while other studies demonstrating increased risk of recurrence and poor survival in gastric cancer patients with high TS expression used 5-FU or tegafur-uracil with or without mitomycin-C (Kuniyasu et al, 1998;Suda et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that thymidylate synthase is the main target for the nucleoside of 5-FU, which binds to the active site of the enzyme in a similar manner to dUMP. This is followed by incorporation of the folate co-factor (Pestalozzi et al, 1997), gastric cancer (Lenz et al, 1995) and primary rectal cancer (Johnston et al, 1994) all reach similar conclusions, with TS expression being measured either immunohistochemically, or using PCR to measure genetic expression of TS mRNA.…”
Section: Nucleoside Analoguesmentioning
confidence: 65%
“…patients with high TS levels have a better outcome with that therapy. This has been seen both in 278 node-positive breast cancer patients receiving CMF (cyclophosphamide, methotrexate, 5-FU) (Pestalozzi et al, 1997) and in 194 patients with Dukes' B and C rectal cancer receiving MOF (methyl CCNU, 5-FU vincristine) chemotherapy (Johnston et al, 1994). The reasons for the apparent paradox are not clear, but the data reported to date would certainly justify further translational studies to clarify the predictive role of TS expression; it remains quite possible that this will vary according to the type of tumour being treated.…”
Section: Nucleoside Analoguesmentioning
confidence: 94%
“…The role of TS in breast cancer remains unclear. 16,17 It has been suggested that TS is weakly associated with the natural history of the disease. 16 No data are available concerning the clinical value of TMK.…”
mentioning
confidence: 99%